2017
DOI: 10.1038/nature23267
|View full text |Cite
|
Sign up to set email alerts
|

Unique roles for histone H3K9me states in RNAi and heritable silencing of transcription

Abstract: Heterochromatic DNA domains play important roles in regulation of gene expression and maintenance of genome stability by silencing repetitive DNA elements and transposons. From fission yeast to mammals, heterochromatin assembly at DNA repeats involves the activity of small noncoding RNAs (sRNAs) associated with the RNA interference (RNAi) pathway1–9. Typically, sRNAs, originating from long noncoding RNAs, guide Argonaute-containing effector complexes to complementary nascent RNAs to initiate histone H3 lysine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
122
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(131 citation statements)
references
References 44 publications
9
122
0
Order By: Relevance
“…Di-and tri-methylation at H3K4 are typical epigenetic signature for gene activation (Jambhekar et al, 2019). The previous study showed that the methylation of H3K9 is associated with transcriptional repressed loci, and that different from H3K9me3 which is associated with transcriptional silence, H3K9me2 is associated with transcriptional activation (Liu et al, 2015;Jih et al, 2017). H3K9me2 loci contain euchromatic transcription associated modifications, and couple transcript degradation via RNAi to the establishment of H3K9 methylation loci (Jih et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Di-and tri-methylation at H3K4 are typical epigenetic signature for gene activation (Jambhekar et al, 2019). The previous study showed that the methylation of H3K9 is associated with transcriptional repressed loci, and that different from H3K9me3 which is associated with transcriptional silence, H3K9me2 is associated with transcriptional activation (Liu et al, 2015;Jih et al, 2017). H3K9me2 loci contain euchromatic transcription associated modifications, and couple transcript degradation via RNAi to the establishment of H3K9 methylation loci (Jih et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The previous study showed that the methylation of H3K9 is associated with transcriptional repressed loci, and that different from H3K9me3 which is associated with transcriptional silence, H3K9me2 is associated with transcriptional activation (Liu et al, 2015;Jih et al, 2017). H3K9me2 loci contain euchromatic transcription associated modifications, and couple transcript degradation via RNAi to the establishment of H3K9 methylation loci (Jih et al, 2017). The results of the study supposed that, mainly by catalyzing the di-and trimethylation of H3K4 and involving the dimethylation of H3K9, AflSet1 up-regulated fungal development, secondary metabolism, and virulence principally via positive regulation of orthodox conidiation, sclerotia formation, and aflatoxin biosynthesis pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Nucleosomes were disrupted and expression of piRNAs and transposons increased, however it was impossible to know which modification was responsible for which function. An independent study found that H3K9me2 and H3K9me3 were functionally distinct in S. pombe where H3K9me2 domains were transcriptionally active and coupled RNAimediated silencing to establish silent H3K9me3 domains (Jih et al 2017). In this study, we examine the defects associated with selective loss of H3K9me3, leaving H3K9me1 and H3K9me2 intact.…”
Section: Introductionmentioning
confidence: 95%
“…A last important holozoan gene regulatory functionality is the "silencing" of gene expression carried by the histone methylating enzymes SUV39H and the Polycomb Group II proteins (Jih et al, 2017). Though acting on the write-read-rewrite mechanism common to all eukaryotes, silencing by methylation is a synapomorphy of Opisthokonta, having arisen in a common ancestor of holozoans and fungi (Kingston and Tamkun, 2014;Steffen and Ringrose, 2014).…”
Section: Eukaryotic-and Holozoan-specific Transcriptional Mechanismsmentioning
confidence: 99%